PENGARUH LATIHAN TERATUR TERHADAP KADAR CIRCULATING ENDOTHELIAL CELLS (CEC) TIKUS STRAIN WISTAR - Rias Gesang Kinanti; Ahmad Abdullah; Mochammad Yunus (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
Circulating endothelial cells (CEC) have been identified as an indication of vascular damage in several diseases, one of which is atherosclerosis coronary heart disease. This study aims to see the effect of regular exercise on CEC levels. The sample used are male rats of the type rattus norvegicus wistar strain, aged 8-10 weeks, body weight 80-110 grams. Healthy rats are taken from specially recommended farms. The total sample consisted of 10 rats, divided into two groups in which the control group consisted of 5 rats and the regular exercise treatment group consisted of 5 rats. Treatment of regular exercise (swimming) for 12 weeks. The finding of this study is that regular exercise can affect the number of Circulating Endothelial Cells (CEC), but the decrease is not significant (p=0.116) compared to the control group. Regular exercise improves endothelial function, characterized by a decrease in the number of CEC.